The Role Of The Lubuk Pakam Correctional Institution In Providing Guidance To Female Prisoners - Yadika Fredera Sebayang; Abdul Razak Nasution (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The correctional system aims to restore prisoners, especially women prisoners, as good citizens, and also aims to protect the community against the possibility of criminal acts by prisoners, especially women prisoners. As well as an application and an integral part of the values contained in Pancasila. From some of the possibilities that occur, the government changed the role to the Correctional Institution, meaning that the convicts are placed together and the placement process and activities according to the schedule since the convict entered the institution, in addition to the length of serving the sentence. Although this institution is not directly related to law enforcement, it plays a major role in creating public order in legal life. This research is focused on literature studies or document studies because this research is mostly carried out on secondary data and Primary Data as a trap, the data to be obtained in this study were collected by means of library research (Library Research) The library material referred to consists of primary legal materials, namely related legislation in accordance with the Criminal Code. The research specification used is descriptive analysis, namely describing the results of research with data that is also complete and as detailed as possible. Description is intended for primary, secondary and tertiary data related to legal certainty about the rights of women prisoners in Lubuk Pakam correctional institutions legislation and theories that have been relevant. The presence of Class IIB Lubuk Pakam Correctional Facility is expected to be able to provide good and appropriate guidance to prisoners and provide information to the public about the implementation of inmate guidance in detention centres through mass media and newspapers or other means in accordance with the intention of changing the public's view of prisoners, that prisoners can return to society without discrimination. The implementation of women prisoners' development in Lubuk Pakam Penitentiary contains several procedures starting from the reception of prisoners, registration to the next stage of the implementation of prisoners' development. In the implementation stage itself consists of stages, namely the initial stage of teaching prisoners to have religious and legal awareness, the advanced stage which gives direction to prisoners to always display their talents and skills so that when in the Penitentiary, prisoners have positive activities to do.